Studi Mad’u dan Teori Resepsi Stuart Hall: Analisis Komentar Netizen pada Ceramah Virtual Buya Yahya - Hakim, Lukman; Dwi Magfiroh, Ervina Putri (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This article reports on the textual thematic research conducted with 100 Netizens' comments on the YouTube channel of Al-Bahjah TV entitled